2024
DOI: 10.1186/s12905-024-03066-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between oxidative balance score and rheumatoid arthritis in female: a cross-sectional study

Rui La,
Liyu Zhou,
Yunfei Yin
et al.

Abstract: Objective Although oxidative stress is a recognized factor of inflammation, the correlation between oxidative balance score (OBS), a biomarker indicating the balance of oxidation and antioxidant, and rheumatoid arthritis (RA), an immune system disease that tends to occur in women, remains unexplored. Hence, the aim of this study was to investigate the potential association between OBS and RA in women. Methods Observational surveys were performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…According to our previous research reports, 24–26 the data concerning arthritis diagnosis was derived from self-reported information obtained during personal interviews with participants. The survey inquired whether a healthcare professional had ever communicated a diagnosis of arthritis to the participant.…”
Section: Methodsmentioning
confidence: 99%
“…According to our previous research reports, 24–26 the data concerning arthritis diagnosis was derived from self-reported information obtained during personal interviews with participants. The survey inquired whether a healthcare professional had ever communicated a diagnosis of arthritis to the participant.…”
Section: Methodsmentioning
confidence: 99%